(untitled) (Research, Society and Development, 2022)
Introduction: gastric bypass is a procedure that revolutionized the history of bariatric surgery, being the most used today and considered the gold standard in this sense, being considered an excellent treatment to achieve weight loss in an adequate and efficient way. durable, with a high success rate and a low rate of adverse effects and complications. Despite its well-documented safety, several complications can occur with different degrees of morbidity and mortality. Objective: to highlight the main surgical complications of gastric bypass. Methodology: this is an integrative literature review. The selection of studies was carried out in April 2022 through a survey of publications indexed in the Virtual Health Library (BVS), Google Scholar, Scientific Electronic Library Online (SciELO) and National Library of Medicine (PubMed MEDLINE) platforms. . Results and discussion: there are complications and risks related to the performance of such a procedure, such as seroma, incisional hernia, deep dehiscence, hematoma, infection, fistula, nutritional deficiencies and cholelithiasis. There are places with an increased possibility for leakage, such as the gastric pouch stapling line, and there are rational factors with a higher incidence of adverse problems, such as advanced age, presence of several comorbidities, prolonged hospital stay, high BMI and sex. feminine. Conclusion: for future complications to be mitigated, it is up to the surgeon to alert himself to the places most susceptible to complications, to evaluate the individual risks and benefits of each patient, analyzing whether surgery is indicated or not, as well as analyzing the risk factors, using tools such as BASIC and ASA.